MEASURING THE LEVEL OF DIGITAL LIBRARY FLUENCY AMONG SCHOLARS IN SAUDI ARABIA- A DESCRIPTIVE ANALYSIS - Daqal , Hussin Ali; Sani , Mad Khir Johari Abdullah; Mohamad , Ahmad Nadzri (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
Following Saudi Arabia’s Vision 2030, Saudi digital libraries have undergone extensive modernization supported by advanced digital infrastructure. Despite these investments, an infrastructure engagement gap has emerged because of insufficient advanced digital competencies among scholars. To examine this issue, a mixed convergent design was used with descriptive techniques, in which digital library fluency was assessed through a survey of 386 scholars (N=386, 95% confidence level) using a scale from one to seven, along with conducting nine interviews with semi-structured questions for key informants at major Saudi research universities. Survey findings revealed a clear competency hierarchy: management competencies were highest (M=6.18), followed by information retrieval and critical thinking skills (M=5.95 each). Notably, a difference of 1.27 points between scholars' ability to use collaboration tools and their collaboration behavior became apparent, as the usage was rated very high (M=6.55, SD=0.92), while peer collaboration (M=5.28, SD=1.44) and shared workspaces (M=5.35, SD=1.38) were found to be significantly lower. Qualitative analysis identified three key barriers: the lack of fluency occurs because of the complex user interface for accessing local repositories, unmodeled senior management, and the presence of reward silos. This implies that digital literacy should be redefined as socio-technical competency at an organizational level.